Clinical staging of malignant pleural mesothelioma: current perspectives - Bonomi M (Dove Medical Press, 2017)
Maria Bonomi,1 Costantino De Filippis,2 Egesta Lopci,3 Letizia Gianoncelli,1 Giovanna Rizzardi,4 Eleonora Cerchiaro,1 Luigi Bortolotti,4 Alessandro Zanello,2 Giovanni Luca Ceresoli1 1Department of Oncology, Thoracic and GU Oncology Unit, 2Department of Radiology, Cliniche Humanitas Gavazzeni, Bergamo, 3Nuclear Medicine Unit, Humanitas Clinical and Research Hospital, Milan, 4Department of Thoracic Surgery, Cliniche Humanitas Gavazzeni, Bergamo, Italy Abstract: Malignant pleural mesothelioma (MPM) is a disease with limited therapeutic options, the management of which is still controversial. Diagnosis is usually made by thoracoscopy, which allows multiple biopsies with histological subtyping and is indicated for staging purposes in surgical candidates. The recommended and recently updated classification for clinical use is the TNM staging system established by the International Mesothelioma Interest Group and the International Association for the Study of Lung Cancer, which is based mainly on surgical and pathological variables, as well as on cross-sectional imaging. Contrast-enhanced computed tomography is the primary imaging procedure. Currently, the most used measurement system for MPM is the modified Response Evaluation Criteria in Solid Tumors (RECIST) method, which is based on unidimensional measurements of tumor thickness perpendicular to the chest wall or mediastinum. Magnetic resonance imaging and functional imaging with 18F-fluoro-2-deoxy-d-glucose positron-emission tomography can provide additional staging information in selected cases, although the usefulness of this method is limited in patients undergoing pleurodesis. Molecular reclassification of MPM and gene expression or miRNA prognostic models have the potential to improve prognostication and patient selection for a proper treatment algorithm; however, they await prospective validation to be introduced in clinical practice. Keywords: malignant pleural mesothelioma, staging, contrast-enhanced computed tomography, magnetic resonance imaging, positron-emission tomography